Ethics of the accountant in front of the social responsibility in Colombia (2014)
This paper reviews some concepts prototype public accountant which significantly influences society, as some from the very nature of being human, to perform its task in a community, looking to the paradigm that created the public accountant as corruptor of organizations, be distorted. Given that the same professional position, make this a community member with a strong influence against social responsibility and ethics within the context of these economic events. This in turn shows that in the middle of the exercise, the accountant is required to be done with the greatest possible transparency services, as the legal and civil consequences are quite impressive, as it were in his professional career, which can reach the loss of his position and credibility in a social environment that shows that raw individual benefit rather than the collective.